Increasing Health Workers’ Knowledge after following Training PDP HIV/AIDS : Health Workers’ Knowledge and Training PDP HIV/AIDS - Herliani, Resda; Wisnuwardani, Ratih Wirapuspita (Universitas Wiralodra, 2025)
Health workers in health facilities have an important role in implementing effective interventions for HIV prevention. Thereore, PDP training is needed for the health workers as an HIV prevention team. The study aimed to evaluate the effective of PDP training to improve the health worker’s knowledge. This study was a pre-experimental study on 211 health workers in 6 districts/cities in East Kalimantan (2 sessions). The training used interactive classroom lecture, role play and practical methods. Data analysis used paired t-test for bivariate (normal distribution data). There was increasing knowledge before and after PDP training (p-value <0.001). It can be concluded that HIV/AIDS PDP training is effective in increasing the knowledge of health workers. HIV/AIDS training for health workers is important to continue to be carried out to increase the activation of new HIV/AIDS PDP services and become one of the HIV prevention efforts.